Congenital muscular dystrophy: brain alterations in an unselected series of Western patients. Issue 4 (April 1991) - Trevisan, C P; Carollo, C; Segalla, P; Angelini, C; Drigo, P; Giordano, R
Abstract : The typical form of congenital muscular dystrophy (CMD) described in Western countries is generally considered different from its Japanese variant because of the absence of CNS involvement. Evaluations from both a clinical and a neuroradiological point of view were made of the CNS functions of 12 unselected Western children affected by CMD. In five patients, clinical observation and intelligence tests showed a mild to severe mental retardation. One of these patients suffered also from a severe form of epilepsy. In the same five patients, various degrees of white matter hypodensity, ventricular enlargement and cerebral atrophy were also detected. Similar neuroradiological abnormalities were also found in five of the seven children who did not have clinical symptoms or signs of CNS involvement. In one of these cases, necropsy neuropathological examination showed the gyral anomalies characteristic of the Japanese type of CMD. This study clearly indicates the high frequency of subclinical CNS alterations in typical Western CMD, suggesting that it should be considered a type of myoencephalopathy like its Japanese counterpart.